Econometric modelling and forecasting of tourism demand methods and applications - Chenguang Wu, Doris; Li, Gang; Song, Haiyan (Routledge, 2023)
"This insightful and timely volume provides a succinct, expert-led introduction to the latest developments in advanced econometric methodologies in the context of tourism demand modelling and forecasting. Embellished with insightful figures and tables throughout, this book is an invaluable resource for those using advanced econometric methodologies in their studies and research, including postgraduate students, researchers and practitioners." --